THE ROLE OF TRANSFORMATIONAL LEADERSHIP IN IMPROVING THE QUALITY OF EDUCATION IN ELEMENTARY SCHOOLS - Nikko, Nikko (International Journal of Teaching and Learning, 2024)
The quality of education in elementary schools is an important factor in developing students' potential and readiness to face future challenges. This research examines the role of transformational leadership in improving the quality of education in elementary schools, through quantitative and qualitative approaches utilizing literature studies, surveys and in-depth interviews in several elementary schools that apply the principles of transformational leadership. Transformational leadership characterized by motivation, inspiration, intellectual stimulation, and individual attention has been proven to positively influence teacher motivation, creativity, and performance, as well as increasing student engagement and academic achievement. This research shows that leaders who are able to inspire, encourage innovation, and pay attention to the needs of individuals in the school community play a key role in creating a conducive educational environment, which in turn improves the overall quality of education. There is a significant relationship between the implementation of transformational leadership practices and improving the quality of education in elementary schools, which is influenced by increasing teacher performance and student academic success. The implications of this research urge the need for leadership education and training for prospective school leaders, with special emphasis on developing transformational leadership qualities, in order to improve the quality of future education.